A bibliometric review of functional ingredients and their efficacy in developing functional biscuits [version 3; peer review: 1 approved, 2 approved with reservations] - Kshama Vishwakarma; Varalakshmi Chandra Sekaran; Vidya Patwardhan; Asha Kamath (F1000Research)
Introduction Numerous studies have concluded that the functional ingredients benefit human health. Similarly, present times have seen exponential growth in functional food in bakery product segments like breads and biscuits. However, there is a lack of information on functional ingredients and their usefulness in developing functional bakery products. This bibliometric study addresses this gap by identifying the current research trends in functional ingredients. Objective To investigate current research trends on functional ingredients and their usefulness in developing functional biscuits. Method The study followed the “Scientific Procedures and Rationales for Systematic Literature Reviews” standards for retrieving literature. The study went through three major stages, “assembling,” “arranging,” and “assessing,” to retrieve 612 articles from the Scopus database from 2013 to 2023. Through further filtering, 395 articles were selected. Result The analysis was conducted using R Studio and VOS viewer. The performance analysis and science mapping tools were used to evaluate the articles. The results showed a 5.76% annual growth in publication trends. The most researched functional ingredients were antioxidants, bioactive compounds, and dietary fiber. The review summarized the most studied foods to develop functional biscuits and highlighted the most experimented technological advancements. Conclusion The study revealed the need for future research studies on functional ingredients with a focus on studying the technical implications of technical advancements in extracting functional ingredients from foods. The study highlights the significance of future studies based on the acceptance of functional biscuits and their sensory properties, focusing on the mass population. The study derives the possible applicability of functional ingredients in developing new formulations from publications and their usefulness in developing new formulations. This insight on the applicability of functional ingredients provides an opportunity for biscuit/cookie manufacturing to boost consumption among the population to a new ascending graph.